What Algebraic Graph Transformations Can Do For Model Transformations - Taentzer, Gabriele (Electronic Communications of the EASST, 2010)
Model transformations are key activities in model-driven development (MDD). A number of model transformation approaches have emerged for different purposes and with different backgrounds.This paper focusses on the use of algebraic graph transformation concepts to specify and verify model transformations in MDD.